Syahadat sebagai jalan spiritual (Analisis Terhadap Nazham-Nazham Sayyid Umar Bin Ismail Bin Yahya) - Radea Yuli Ahmad Hambali; Dedi Slamet Riyadi (Fakultas Ushuluddin UIN Sunan Gunung Djati Bandung, 2022)
This article presents a study of two sentences of shahada (syahadatain) which in Islamic teachings are positioned as the basis of diversity. However, most jurisprudence books begin their description of Islamic teachings with the chapter Thâhârah - purification. This condition causes the study of the two sentences of the creed to not develop among academics. The distinctive position of the two sentences of the creed is actually commonly discussed in the world of Sufism. Jalaluddin Rumi, al-Jilli, al-Haddad, as well as the philosopher-poet Muhammad Iqbal have commented specifically on these two sentences of the creed. This article intends to explore the Asy-Syahadatain Order which specifically places two sentences of the creed as a starting point for spiritual practice. This study uses discourse analysis through literature searches of books, especially books of the nazham collection of Sayyid Umar bin Ismail bin Yahya. The findings of this study indicate that there are different meanings and treatments of the two creed in the Asy-Syahadatain order. In contrast to other tarekat, in its dhikr ritual, the Asy-Syahadatain tarekat chooses two sentences of the shahada, plus the sentence of prayer to the Prophet, his family and friends -as the initial sentence chanted after greeting in prayer. Not only that, this tarekat makes the creed as the basis for the journey of a traveler on the spiritual path (salik).